Analisis Strategi Pemasaran Toko Online Dalam Meningkatkan Penjualan - Dian Martha Darman; Marro’aini Marro’aini; Lita Arfah; Nursakinah Nursakinah (Universitas Negeri Makassar, 2026)
E-commerce is a place where transactions or exchanges of information occur between sellers and buyers in the virtual world. The MSME sector in Pekanbaru City is currently showing quite significant growth. There was an increase in the number of MSMEs in 2024, reaching 26,684 units. One of the MSMEs operating in the Muslimah fashion sector is Handsqob Onlineshop. Therefore, this research aims to conduct an in-depth analysis of the digital marketing strategies implemented by Handsqob Onlineshop across various digital platforms in order to design effective, innovative, and competitive marketing strategies amidst increasingly fierce competition. The research method in this study uses a qualitative approach with the application of SWOT analysis to determine the marketing strategy at Handsqob Onlineshop. Based on the SWAT analysis conducted, the best step that can be taken is to implement the SO (Strengths–Opportunities) strategy, which involves utilizing all the strengths possessed to seize the existing opportunities. This can be achieved through the optimization of digital marketing, strengthening collaborations with influencers, and developing product lines that meet market needs